A Pilot Randomized Trial of a Video Patient Decision Aid to Facilitate Early Intervention Referrals From Primary Care. (March 2017) - Jimenez, Manuel E.; DuRivage, Nathalie E.; Bezpalko, Orysia; Suh, Andrew; Wade, Roy; Blum, Nathan J.; Fiks, Alexander G.
Many young children identified with developmental concerns in pediatric settings do not receive early intervention (EI). We assessed the impact of a video decision aid and text message reminder on knowledge and attitudes regarding developmental delay and EI as well as referral completion. We conducted a pilot randomized controlled trial in an urban setting and enrolled 64 parent-child dyads referred to EI. Compared with controls, participants who received the intervention demonstrated increased knowledge regarding developmental delay and EI as well as more favorable attitudes in certain topics. Although we did not find a significant difference between arms in EI intake and evaluation, we found a pattern suggestive of increased intake and evaluation among participants with low health literacy in the intervention arm. Additional study is needed to identify strategies that improve the EI referral process for families and to understand the potential targeted role for decision aids and text messages.